Components for a combinatorial library of rigid azabicyclic alpha-L-fucose mimics: First X-ray crystal structure of a stable monoalkylated triazene formed by hydrogenation of an azide - Smelt, K; Harrison, A; Biggadike, K; Muller, M; Prout, K; Watkin, D; Fleet, G (1999)
Photobromination of the rigid, aza-bicyclic fucose mimic 3 gave a reactive glycosyl type bromide 7 as a divergent intermediate for the synthesis of both 7-0 and 7-N linked bycyclic L-fucose derivatives by direct displacement with alcohols or amines. Displacement of the bromide 7 with sodium azide gave an azide 6 which on hydrogenation gave a stable monoalkyl triazene 5, the structure of which was established by-X-ray crystallographic analysis. Hydrolysis of 7 allowed access to a monocyelic L-fucose mimic with a nitrogen substituent at C-5.